Analisa Laporan Keuangan untuk Menilai Kinerja Perusahaan : (Studi Pada Perusahaan Sub Sektor Semen yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Athiy Dina Rosihana (Jurnal Publikasi Ilmu Manajemen, 2023)
This research was conducted to determine and assess the financial performance of cement sub-sector companies listed on the IDX in 2020-2022. This research uses quantitative descriptive research methods. The financial ratio analysis used uses profitability ratios, liquidity ratios, solvency ratios and activity ratios. The results of the research show that overall the financial performance of cement sub-sector companies is in good condition, only the WSBP company whose financial performance is not good. So the WSBP company needs to improve its financial performance so that the company's value increases in the eyes of investors.